2012
DOI: 10.1258/jhsrp.2011.011046
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Governance of Autonomous Public Hospitals in England: Multi-Site Case Study of NHS Foundation Trusts

Abstract: It is easier to increase autonomy for public hospitals than to increase local accountability. Hospital managers are likely to be interested in making decisions with less central government control, whilst mechanisms for local accountability are notoriously difficult to design and operate. Further consideration of internal governance of FTs is needed. In a deteriorating financial climate, FTs should be better placed to make savings, due to their more business-like practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…This process was accelerated after 2003, with the introduction of a new organisational form: Foundation Trusts (FTs). Conforming to the model of corporatisation described earlier (Lindlbauer et al 2015), FTs remain part of the NHS (and hence in public ownership), but are re-designated as public benefit corporations with significantly more formal autonomy than the other NHS trusts (Allen et al 2012). …”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was accelerated after 2003, with the introduction of a new organisational form: Foundation Trusts (FTs). Conforming to the model of corporatisation described earlier (Lindlbauer et al 2015), FTs remain part of the NHS (and hence in public ownership), but are re-designated as public benefit corporations with significantly more formal autonomy than the other NHS trusts (Allen et al 2012). …”
Section: Research Contextmentioning
confidence: 99%
“…Applying trusts need to show that they have a number of controls, checks and assurances processes and procedures in place, ranging from trust financial viability to effective quality and safety checks. Most importantly, authorisation to become an FT is 20 conditional on performance, this initially being branded as a form of 'earned autonomy' (Allen et al 2012). The independent regulator, Monitor (responsible for providing authorisation), concentrates on the efficiency of organisational processes and the fitness-for-purpose of the governance arrangements.…”
Section: Research Contextmentioning
confidence: 99%
“…Estudos internacionais vêm discutindo os impactos da autonomia em estabelecimentos públicos, principalmente no âmbito hospitalar 6,7 , em que também no Brasil identifica-se a maior prevalência de autonomia pública. Para Paim 8 , baixa autonomia financeira na administração direta da saúde é uma questão central no SUS, e ainda hoje pode atingir inclusive órgãos gestores, como secretarias de saúde.…”
Section: Discussionunclassified
“…Allen et al (2012) studied the development and governance of NHS Foundation Trusts, finding that they had used their increased vertical autonomy to introduce more business-like practices, with regulators only intervening when problems were reported. However, national-level targets continued to have a significant impact on their work, and they were also constrained horizontally by the need to maintain good relationships with local organisations.…”
Section: Autonomy and Decision Space In The Nhsmentioning
confidence: 99%
“…However, national-level targets continued to have a significant impact on their work, and they were also constrained horizontally by the need to maintain good relationships with local organisations. It was intended that Foundation Trusts would manifest additional local accountability, with governance by local 'members', but this has proved problematic to realise in practice (Allen et al, 2012). Exworthy et al (2011) studied Foundation Trusts' willingness and ability to exercise autonomy at three levels: macro; meso; and micro, and found that, whilst they had theoretically gained autonomy from central control, in practice, new forms of economic regulation had partially replaced the previous NHS hierarchy, with Foundation Trusts held to account by Monitor (a health care provider financial regulator, since April 2016 known as NHS Improvement) through a variety of performance and assessment mechanisms.…”
Section: Autonomy and Decision Space In The Nhsmentioning
confidence: 99%